Pengaruh Variasi Diameter Media Untuk Penyisihan Beban Polutan Limbah Cair Domestik Dalam Moving Bed Biofilm Reactor (MBBR) Dengan Memanfaatkan Biocarrier Limbah Sedotan Plastik - Insani, Suciati Dwi; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Domestic waste water is one of the main cause of river pollution. Grey water gives about 75-90% the pollution of surface water. The treatment that can be done is to use biomass, one of which is microalgae Chlorella sp. In this Study, the addition of biocarriers made from plastic straws as a medium for attaching microorganism using MBBR process. The variation is diameter of biocarrier that is 0,5 inch, ¾ inch, and 1inch which inserted into the reactor with working volume of 3 liters, air supply 4 liters/minute, the volume of biocarrier is 30% of the reactor volume, and the contact time is 0,1,3,5,7 days. The result of the study, obtained the best removal for 67.3% COD, 83.27% TSS on the reactor filled with biocarrier 0.5 inch on day 7. It shows that the smaller diameter of the growing media produces the highest efficiency.Keywords : MBBR, Plastic Straw Biocarrier, Chlorella sp., Domestic Waste Water,Ammonia